The Ideological Choices in the English-Indonesian Translation of Imperative Utterances in Al-Quran Surah Al-Kahf - Moh. Gufron Rajabul; Siti Wahyu Puji Anggraini Anggraini; Rospin Hidayati (Humanitatis : Journal of Language and Literature, 2026)
This study is grounded in the increasing need to understand how ideological perspectives shape the translation of sacred texts, particularly in the rendering of directive expressions across languages. The complexity of translating imperative utterances lies in preserving both their directive force and theological meaning. In Qur’anic discourse, imperative utterances carry not only linguistic meaning but also theological, cultural, and pragmatic significance, making their translation highly complex and ideologically sensitive. Therefore, this study aims to investigate the translation ideology underlying the English–Indonesian rendering of imperative utterances in Surah Al-Kahf, with a particular focus on identifying their thematic distribution and examining how they are translated through the frameworks of domestication and foreignization proposed by Lawrence Venuti. Employing a qualitative discourse analysis approach, this study analyzes 44 imperative utterances extracted from the English translation by Mustafa Khattab and the Indonesian translation issued by the Ministry of Religious Affairs. The data were systematically classified and analyzed based on thematic categories and translation ideology. The findings reveal that the imperative utterances are organized into three major thematic domains: theological orientation, moral-psychological formation, and pragmatic-life guidance. These imperatives function as complex directive speech acts, encompassing guidance, warnings, instructions, and ethical formation. In terms of translation ideology, 35 out of 44 utterances are translated using domestication, while 9 reflect foreignization. Domestication predominates in the moral and pragmatic domains, where clarity, naturalness, and cultural familiarity are prioritized. In contrast, foreignization is selectively applied in theological contexts to preserve the rhetorical structure, lexical specificity, and sacred tone of the source text.